2020
DOI: 10.1021/acsnano.9b08835
|View full text |Cite
|
Sign up to set email alerts
|

Rare Earth Single-Atom Catalysts for Nitrogen and Carbon Dioxide Reduction

Abstract: Single-atom catalysts (SACs) have attracted much attention owning to their high catalytic properties. Herein, yttrium and scandium rare earth SACs are successfully synthesized on a carbon support (Y1/NC and Sc1/NC). Different from the well-known M–N4 structure of M–N–C (M = Fe, Co) catalysts, Sc and Y atoms with a large atomic radius tend to be anchored to the large-sized carbon defects through six coordination bonds of nitrogen and carbon. Although Y- and Sc-based nanomaterials are generally inactive to room-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
182
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 225 publications
(190 citation statements)
references
References 58 publications
1
182
0
Order By: Relevance
“…The simultaneous coordination method has been successfully used to prepare several SACs of Fe/Y/Sc‐N‐C. [ 16c,17 ] Using this method, PM chlorides and ZnO were simultaneously mixed with 2MI, sealed in a Teflon‐lined stainless autoclave under Ar protection, and finally heat‐treated at 220 °C for 18 h to obtain PM‐loaded ZIF (named as PM/ZIF‐simu). X‐ray diffraction (XRD) patterns of PM/ZIF‐simu (PM = Rh, Pd, Pt) are similar to that of pristine ZIF‐8, except that a small new peak appears at 2θ = 13.9° for Ir/ZIF‐simu (Figure 1b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The simultaneous coordination method has been successfully used to prepare several SACs of Fe/Y/Sc‐N‐C. [ 16c,17 ] Using this method, PM chlorides and ZnO were simultaneously mixed with 2MI, sealed in a Teflon‐lined stainless autoclave under Ar protection, and finally heat‐treated at 220 °C for 18 h to obtain PM‐loaded ZIF (named as PM/ZIF‐simu). X‐ray diffraction (XRD) patterns of PM/ZIF‐simu (PM = Rh, Pd, Pt) are similar to that of pristine ZIF‐8, except that a small new peak appears at 2θ = 13.9° for Ir/ZIF‐simu (Figure 1b).…”
Section: Resultsmentioning
confidence: 99%
“…Scientists have developed strategies for doping (replacing Zn with foreign metal ions) and encapsulating (capturing foreign metal ions in the micropores) non‐precious transition metals (Fe, Co, Ni, etc.) [ 16 ] and rare earths (Y, Sc) [ 17 ] into ZIF‐8, which can be converted into carbon‐supported nitrogen‐coordinated SACs with 2–3 wt% metal after pyrolysis. However, the conventional doping strategy is not effective for PM probably because of the weak competitiveness or excessive ion size of PM compared to zinc.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al found that rare earth yttrium (Y) and scandium (Sc) atoms with large atomic radius tend to coordinate with three nitrogen and three carbon atoms (Y/Sc‐N 3 C 3 ) at large‐scale carbon defects rather than the well‐known SA‐N 4 structure. [ 100 ]…”
Section: Design Principles For Sasmentioning
confidence: 99%
“…Density functional theory (DFT) calculations have been used to analyze the formation energy of the atomic active site and the adsorption energy of O 2 , ORR reaction intermediates on the active site, which can be used to judge the feasibility of active sites for ORR and analyze the reaction process at these sites [27–29] . The formation of phosphorus‐coordinated atomic metal M−P x embedded in graphene, such as Fe−P 4 and Co−P 4 , has been calculated energetically feasible [12] .…”
Section: Theoretical Advancesmentioning
confidence: 99%